Modulating the proliferative and cytotoxic properties of patient-derived TIL by a synthetic immune niche of immobilized CCL21 and ICAM1 - Yunger, Sharon; Geiger, Benjamin; Friedman, Nir; Besser, Michal J.; Adutler-Lieber, Shimrit (Frontiers in Oncology, 2023)
A major challenge in developing an effective adoptive cancer immunotherapy is the ex-vivo generation of tumor-reactive cells in sufficient numbers and with enhanced cytotoxic potential. It was recently demonstrated that culturing of activated murine CD8+ T-cells on a “Synthetic Immune Niche” (SIN), consisting of immobilized CCL21 and ICAM-1, enhances T-cell expansion, increases their cytotoxicity against cultured cancer cells and suppresses tumor growth in vivo. In the study reported here, we have tested the effect of the CCL21+ICAM1 SIN, on the expansion and cytotoxic phenotype of Tumor Infiltrating Lymphocytes (TIL) from melanoma patients, following activation with immobilized anti-CD3/CD28 stimulation, or commercial activation beads. The majority of TIL tested, displayed higher expansion when cultured on the coated SIN compared to cells incubated on uncoated substrate and a lower frequency of TIM-3+CD8+ cells after stimulation with anti-CD3/CD28 beads. Comparable enhancement of TIL proliferation was obtained by the CCL21+ICAM1 SIN, in a clinical setting that included a 14-day rapid expansion procedure (REP). Co-incubation of post-REP TIL with matching target cancerous cells demonstrated increased IFNγ secretion beyond baseline in most of the TIL cultures, as well as a significant increase in granzyme B levels following activation on SIN. The SIN did not significantly alter the relative frequency of CD8/CD4 populations, as well as the expression of CD28, CD25, several exhaustion markers and the differentiation status of the expanded cells. These results demonstrate the potential capacity of the CCL21+ICAM1 SIN to reinforce TIL-based immunotherapy for cancer patients.